Growth and Nutrient uptake of Sporobolus helvolus under different Edaphic Conditions - Dutta, B K (Annals of Arid Zone, 2016)
Sporobolus helvolus, a major forage grass of saline tract, was studied in pot culture for its growth and nutrient uptake under various edaphic conditions. Plant height and dry matter production were maximum in soil collected from Pachpadra salt-basin and tank silt. But its growth was poor in alluvial soil. In Pachpadra SOil the root showed less growth than that of tank silt and alluvial soil. The relative nutrient uptake pattern in different soils has been discussed.